Pemanfaatan Limbah Kayu Kopi Sebagai Bahan Perancangan Perabot Gereja Kristen Jawi Wetan di Jengger Kabupaten Malang - Ruben Christianto Driyomartono; Andereas Pandu Setiawan; Frenky Tanaya (Intra, 2019)
The furniture design for a church by utilizing coffee wood waste is a design research that aims to equalize the use of woods in Indonesia today. This is caused by the increase in rarity of the types of woods that are often used in Indonesia. One of the alternative woods which can reduce the use of these rare woods are coffee woods. Coffee woods were chosen because of their large amount of availability in Indonesia whereas these woods are considered as wastes for the surrounding community especially when the plant is already at an unproductive state. Based on this issue, there are exceptional opportunities by using coffee wood to be designed into goods which has more values, especially when designed into furniture and interior elements, this is because coffee woods has the same characteristics with woods that are used for general furniture. In this design research, studies and researches about coffee woods are being conducted, which are all related to processing the raw material into finished goods, as well as constructions, strengths and weaknesses of the material, etc, which all of these has the purpose to increase the value and function of coffee woods. By doing this furniture design, it is expected that coffee wood waste can be recycled into more valuable goods, and also to equalize the use of other types of wood, so that the scarcity of other types of woods can be mitigated.